Sejarah Masuknya Islam di Andalusia - Nurul Hafidzah; Nasril Nasril (Universitas Palan, 2025)
Before the arrival of Islam, Andalusia, which is now part of Spain, experienced various phases of power and conflict. The region was originally under the control of the Roman Empire and was known as Iberia. . After the Roman period, the Vandals controlled the region, so it became known as Vandalusia. This study aims to analyze the history of the entry of Islam in Andalusia. The research method used is library research where data sources are obtained from books, articles, journals and other readings. With this research, it can produce knowledge about the process of Islamic entry in Andalusia.